High-Temperature Performance Analysis of AlGaN/GaN Polarization Doped Field Effect Transistors Based on the Quasi-Multi-Channel Model - 房玉龙 冯志红 李成明 宋旭波 尹甲运 周幸叶 王元刚 吕元杰 蔡树军 (Chinese physics letters, 2015)
We report on the temperature-dependent dc performance of A1GaN/GaN polarization doped field effect transistors （PolFETs）. The rough decrements of drain current and transeonductance with the operation temperature are observed. Compared with the conventional HFETs, the drain current drop of the PolFET is smaller. The transeonductance drop of PolFETs at different gate biases shows different temperature dependences. From the aspect of the unique carrier behaviors of graded AlGaN/GaN heterostructure, we propose a quasi-multi-channel model to investigate the physics behind the temperature-dependent performance of AlGaN/GaN PolFETs.